Interaction between tacit and codified knowledge in socio-spatial context. (1st March 2014) - Cohendet, Patrick
Abstract : Patrick Cohendet was previously dean of the Faculty of Economics at Strasbourg University (1982–1985), vice president of the University of Strasbourg (1991–1992), member of the Conseil des Applications de l'Académie des Sciences in Paris (1994–2002), and chairman of the International Business Department at HEC Montréal (2007–2008). He was also visiting professor at the University of Virginia, and the University of Tokyo. His research interests include the theory of the firm, economics of innovation, economics of knowledge, economics of creativity and knowledge management.